Cultural Environmentalism and the Constructed Commons. - Van Houwelling, Molly Shaffer (Law & Contemporary Problems)
Part of a special issue commemorating ten years of cultural environmentalism. Advocates for the value of open access to cultural raw materials are increasingly borrowing protective measures from the environmental lobby. One such measure is the “conservation easement,” which conveys non-possessory property rights to the owner of land, typically a charitable trust or government body, on condition that the land be conserved. In a similar vein, public domain advocates have developed efforts such as the General Public License, which allows free copying and adaptation of copyrighted computer software on condition that the resulting copies and adaptations are licensed on the same terms and accompanied by their source code. The writer examines these tools of cultural environmentalism in light of objections to conservation easements and broader concerns with complex and fragmented property rights.